True Cowmen and Commercial Farmers: Exploring Vets' and Dairy Farmers' Contrasting Views of 'Good Farming' in Relation to Biosecurity. Issue 3 (22nd January 2018) - Shortall, Orla; Sutherland, Lee‐Ann; Ruston, Annmarie; Kaler, Jasmeet
Abstract: Responsibility for biosecurity in UK farming is being devolved from government to industry, with a greater emphasis on the veterinarian (vet)‐farmer relationship. Although social science has shown that care for animals is part of 'good farming', the British dairy sector sees a need to improve biosecurity. This research uses the good farmer concept to compare how vets and dairy farmers define good farming for biosecurity based on qualitative interviews with 28 vets and 15 dairy farmers in England. The results revealed two conflicting 'good farmer' identities: the large, commercial farmer who has the economic capital to invest in biosecurity and veterinary services; and the self‐sufficient stock keeper whose cultural and social capital lead them to manage herd health independently. These identities reflect changing 'rules of the game', following Bourdieu's use of the term, and increasing penetration of vets' cultural capital into the sector. They involve different constructions of risk which need to be recognised within debates about good biosecurity.